Exploring the composition of the Pentateuch - Baker, Leslie Scott Jr. 1973-; Bergland, Kenneth; Masotti, Felipe A. 1984-; Wells, A. Rahel (University Park, PA Penn State University Press, 2021)
Frontmatter -- Contents -- Preface . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . -- List of Abbreviations -- Introduction -- Contributors -- Part 1. History of Scholarship and Alternative App roaches -- Chapter 1. A Critical Intellectual History of the Historical-Critical Paradigm in Biblical Studies -- Chapter 2. The Exodus, Debt Slavery, and the Composition of the Pentateuch -- Chapter 3. Egyptian Language Practice: A Model for Hebrew Poetic Use? -- Chapter 4. Second-Millennium BC Cuneiform from the Southern Levant and the Literature of the Pentateuch -- Chapter 5. The Hittite Treaty Prologue Tradition and the Literary Structure of the Book of Deuteronomy -- Chapter 6. Memorized Covenantal Instruction and Legal Reuse in Torah -- Chapter 7. The Liturgical Function of Dates in the Pentateuch -- Part 2. Exegetical Studies -- Chapter 8. In the Tradition of Moses: The Conceptual and Stylistic Imprint of Deuteronomy on the Patriarchal Narratives -- Chapter 9. Was Moses the Last Prophet? An Analysis of a Neo-Documentarian Interpretation of Document E -- Chapter 10. Revisiting the Literary Structure(s) of Exodus -- Chapter 11. Was Leviticus Composed by Aaronide Priests to Justify Their Cultic Monopoly? -- Chapter 12. The Reception of Priestly Laws in Deuteronomy and Deuteronomy’s Target Audience -- Chapter 13. The Relevance of Ezekiel and the Samaritans for Pentateuchal Composition: Converging Lines of Evidence -- Bibliography -- Ancient Source Index -- Subject Index
For many years, the historical-critical quest for a reconstruction of the origin(s) and development of the Pentateuch or Hexateuch has been dominated by the documentary hypothesis, the heuristic power of which has produced a consensus so strong that an interpreter who did not operate within its framework was hardly regarded as a scholar. However, the relentless march of research on this topic has continued to yield new and refined analyses, data, methodological tools, and criticism. In this spirit, the contributions to this volume investigate new ideas about the composition of the Pentateuch arising from careful analysis of the biblical text against its ancient Near Eastern background.Covering a wide spectrum of topics and diverging perspectives, the chapters in this book are grouped into two parts. The first is primarily concerned with the history of scholarship and alternative approaches to the development of the Pentateuch. The second focuses on the exegesis of particular texts relevant to the composition of the Torah. The aim of the project is to foster investigation and collegial dialogue in a spirit of humility and frankness, without imposing uniformity.In addition to the editors, the contributors include Tiago Arrais, Richard E. Averbeck, John S. Bergsma, Joshua A. Berman, Daniel I. Block, Richard Davidson, Roy E. Gane, Duane A. Garrett, Richard S. Hess, Benjamin Kilchör, Michael LeFebvre, Jiří Moskala, and Christian Vogel
[Online-Ausgabe]
Mode of access: Internet via World Wide Web.
In English
Keywords: RELIGION / Biblical Studies / Old Testament; RELIGION / Biblical Criticism & Interpretation / Old Testament; LITERARY CRITICISM / Jewish; RELIGION / Judaism / General; Composition; Pentateuch; Torah; pentateuchal studies; Documentary Hypothesis